IMPROVING STUDENTS’ PARTICIPATION IN SPEAKING ENGLISH USING TALK SHOW TECHNIQUE - Aprila, Fippi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThis research was done to know how the use of Talk Show technique can improve students’ participation in speaking English. The form of this research was a classroom action research, in which the subject is the first grade students (X IPA 1) of SMA N 1 Sungai Raya in academic year 2016/2017. The data were collected using observation checklist, field notes, and recorders. The students’ participation were observed, calculated, analyzed, and classified. The result of this research showed that the students’ participation in each cycle has improved during their discussion and performance of their talk shows. The improvement can also be seen through the percentages: 47% (poor) for discussion and 85% (excellent) for performance on the first cycle and improved again to 67% (good) for discussion and 84% (excellent) for performance on the second cycle. In conclusion, the findings from the observation checklist and field notes confirmed that the use of Talk Show technique can improve students’ participation. Keywords: Participation, Speaking English, Talk Show Technique AbstrakPenelitian ini dilakukan untuk mengetahui bagaimana pengaplikasian teknik Talk Show dapat meningkatkan partisipasi siswa dalam berbicara Bahasa Inggris. Bentuk dari penelitian ini adalah penelitian tindakan kelas, yang mana subjeknya adalah siswa kelas satu (X IPA 1) di SMA N 1 Sungai Raya pada tahun ajaran 2016/2017. Data dikumpulkan menggunakan daftar observasi, catatan lapangan, dan alat rekam. Partisipasi siswa diobservasi, dihitung, dianalisis, dan diklasifikasikan. Hasil dari penelitian ini menunjukkan bahwa partisipasi siswa pada setiap siklus meningkat pada saat diskusi dan penampilan talk show mereka. Peningkatannya juga dapat dilihat melalui persentasenya: 47% (buruk) untuk diskusi dan 85% (luar biasa) pada penampilan di siklus pertama dan meningkat lagi menjadi 67% (bagus) untuk diskusi dan 84% (luar biasa) pada penampilan di siklus kedua. Kesimpulannya, hasil temuan dari daftar observasi dan catatan lapangan mengkonfirmasi bahwa penggunaan teknik Talk Show dapat meningkatkan partisipasi siswa. Kata Kunci: Partisipasi, Berbicara dalam Bahasa Inggris, Teknik Talk Show